ANALISIS FAKTOR YANG MEMPENGARUHI MINAT KUNJUNGAN DI TAMAN MARGASATWA SEMARANG - Heri Prabowo (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2019)
This study aims to determine whether there is a positive and significant influence between thepromotion of mix and location of interest in Semarang Wildlife Park, and to find out which variableis the most dominant influence on visiting interest. The tools in this study were interviews,questionnaires, observations and documentation. The number of samples in this study were 70respondents in Semarang Wildlife Park. The conclusion of this research is the promotion mixvariable influences the interest of the visit, but the location variable has no effect on the interestof the Semarang Wildlife Park visit.